Pengembangan Kemampuan Tour Guide Desa Warnasari Kecamatan Pengalengan Kabupaten Bandung - Alif Oktavia (Kaibon Abhinaya, 2020)
The Warnasari Village Tourism Area is a place that offers the attraction of natural scenery and stretches of plantations. The Warnasari Village Tourism Area is projected by the Bandung Regency Culture and Tourism Office as one of the leading tourist destinations in South Bandung. The purpose of this activity is to improve the ability of the Tour Guide of Warnasari Village, Pengalengan District, Bandung Regency.